Determinants of return to HIV treatment after interruption on ART among HIV positive clients in Katakwi District, Uganda - William Okello; Saadick Mugerwa Ssentongo; Bonniface Oryokot; Baker Bakashaba; Ronald Opito; Bosco Opio; Christine Acio (PLoS ONE, 2026)
Background Returning to treatment following interruptions is crucial for achieving optimal HIV care outcomes. In Uganda, despite a 20% treatment interruption rate, only 58% of clients successfully resume treatment. Evidence on determinants of returning to treatment remains limited. This study aimed to identify determinants of return to HIV treatment after interruption in Katakwi District, Uganda. Methods We conducted a cross-sectional study at three high-volume antiretroviral therapy (ART) clinics in Katakwi District. Data were collected using face-to-face interviews from study adult participants and analyzed using Poisson generalized estimating equations (GEE) with robust standard errors to identify factors independently associated with a return to care. Results The rate of return to care was 63.9%. Clients without an occupation were less likely to return (aRR = 0.80, 95% CI: 0.73–0.88, p < 0.001). Surprisingly, those living within 5 km of a facility were also less likely to return compared to those 5–10 km away (aRR = 0.78, 95% CI: 0.63–0.95, p = 0.019). Positive community beliefs about treatment adherence significantly increased the likelihood of returning (aRR = 1.18, 95% CI: 1.06–1.33, p = 0.003), as did belonging to a community support group (aRR = 1.16, 95% CI: 1.01–1.39, p = 0.04). Conclusion Return to HIV care was associated with occupation, distance to the facility, community beliefs, and belonging to a community support group. Interventions to improve re-engagement should include targeted economic support for unemployed clients, community-based anti-stigma campaigns, flexible clinic hours, and improved rural access through mobile clinics. Continuous client education at both the facility and community levels is essential.